Cost-driven motives to relocate manufacturing abroad among small- and medium-sized manufacturers: The influence of Industry 4.0. Issue 3 (25th February 2020) - Stentoft, Jan; Wickstrøm, Kent Adsbøll; Haug, Anders; Philipsen, Kristian
Abstract : Purpose: The purpose of this paper is to advance the understanding of how Industry 4.0 related technologies affect the relocation of manufacturing abroad by small and medium-sized enterprises. Design/methodology/approach: This paper contains an empirical analysis of how Industry 4.0 related technologies affect the cost-driven relocation of manufacturing abroad based on 191 comprehensive and full responses to a questionnaire survey distributed in 2018 among small- and medium-sized Danish manufacturers. Findings: This paper builds upon data, which reveals that companies' pursuit of cost-focused competitive strategies is positively correlated with relocating manufacturing abroad. However, the data also shows that the more Industry 4.0-ready decision-makers are, the less cost-focused strategy drives manufacturing abroad. Furthermore, perceived barriers to Industry 4.0 related technologies promote the cost-driven relocation of manufacturing abroad whereas perceived drivers decrease this phenomenon. Research limitations/implications: This paper is based on the answers given by a single respondent from each company and only on Danish respondents. Practical implications: The results indicate a need to invest resources to obtain a better knowledge of Industry 4.0 related technologies when used in processes involved in decisions about where to locate manufacturing. Originality/value: This paper contains new, empirically founded information about how Industry 4.0 related technologies affect the cost-driven relocation of manufacturing abroad from the perspective of small- and medium-sized manufacturers.